An engineering perspective on the future role of modelling in proton exchange membrane water electrolysis development. (June 2022) - Bensmann, Boris; Rex, Alexander; Hanke-Rauschenbach, Richard
Abstract : The development of proton exchange membrane water electrolysis for hydrogen production to satisfy the industrial demand regarding scale, performance and lifetime is challenging. The objectives with the highest priority are a reduction of the power-specific cost and increases in efficiency, reliability, and durability. The main drivers for technology development are usually ex situ and in situ experiments with new or customised materials at various operating conditions. However, modelling was already able to support technology development in the past and will even gain more importance in future. This article looks at the importance of modelling for further development from an engineering perspective and therefore focuses on the macroscopic and microscopic levels. It is stated that the advances in computational engineering and digitalisation in combination with the trend to machine learning/artificial neural networks may even lead to more intensive use of models. Highlights: Perspectives of future role of modelling in PEMWE are given. Use of physics-based neural networks for PEMWE is analysed. Classification for elements in PEMWE modelling is suggested.